PENGARUH GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILTY, KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PERUSAHAAN SEKTOR MANUFAKTUR SUB SEKTOR MAKANAN & MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE (2022 – 2024) - Elis Rahmawati; Soemaryono Soemaryono (CV. Denasya Smart Publisher, 2026)
This study analyzes the effect of green accounting, Corporate Social Responsibility (CSR), and financial performance on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This study employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and PROPER data. The sampling technique used was purposive sampling, resulting in 49 companies with a total of 147 observations. Data were analyzed using multiple linear regression with the assistance of SPSS version 23. The results indicate that green accounting has a negative and significant effect on firm value, CSR has no effect on firm value, while financial performance has a positive and significant effect on firm value. Simultaneously, green accounting, CSR, and financial performance have a significant effect on firm value.